2011
DOI: 10.1007/s00432-011-1033-x
|View full text |Cite
|
Sign up to set email alerts
|

GPx-1 polymorphism (rs1050450) contributes to tumor susceptibility: evidence from meta-analysis

Abstract: These results suggest that the GPx-1 Pro198Leo polymorphism contributes to cancer susceptibility through a disturbed antioxidant balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The Asian population in our database had a zero T allele frequency, while the Maori and Pacific populations showed a frequency of 0.04, similar to that of Asian populations reported by Chen et al [20]. The Indian and Middle Eastern group had a T allele frequency of 0.25, which is within the range reported for Europeans [20]. Therefore, the current subject selection for the analysis was based on the GPx1 rs1050450 T allele frequency distribution (similar to that of Europeans reported by Chen et al) and included subjects self-reporting as Indian sub-continent and Middle Eastern origins, along with those reporting a European origin.…”
Section: Methodssupporting
confidence: 66%
See 3 more Smart Citations
“…The Asian population in our database had a zero T allele frequency, while the Maori and Pacific populations showed a frequency of 0.04, similar to that of Asian populations reported by Chen et al [20]. The Indian and Middle Eastern group had a T allele frequency of 0.25, which is within the range reported for Europeans [20]. Therefore, the current subject selection for the analysis was based on the GPx1 rs1050450 T allele frequency distribution (similar to that of Europeans reported by Chen et al) and included subjects self-reporting as Indian sub-continent and Middle Eastern origins, along with those reporting a European origin.…”
Section: Methodssupporting
confidence: 66%
“…It is possible that the increased GPx activity among GPx1 rs1050450 allele T is a feature dependent on the prostate cancer pathway. A meta-analysis carried out in 14,372 cases with different tumour types and 18,081 controls derived from 31 published case-control studies has indicated that individuals with GPx1 rs1050450 CT and TT genotypes are at high risk for overall cancer incidence [20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic study comprised the analysis of nine tag polymorphisms (http://www.broadinstitute.org/mpg/tagger/ server.html) of three genes of the enzymes of the ADS with the use of DNA real-time polymerase chain reaction (RT-PCR). These polymorphisms were selected, because it was shown that they are significant in other diseases, such as neoplasms, in which oxidative stress plays important role in etiopathogenesis [13]. Real-time PCR was performed using protocol provided by Applied Biosystem to assess rs1041740, rs4998557 and rs2070424 SNPs of the SOD1 gene, rs2855116, rs5746136 and rs4880 SNPs of the SOD2 gene and rs3448, rs1050450 and rs1800668 SNPs of the GPx-1 gene.…”
mentioning
confidence: 99%